(untitled) (PerCursos, 2021)
Eurocentric thinking, with a dualistic basis of balance and two weights, in Aristotelian logic and Euclidean and Cartesian Geometry, was strongly criticized by intellectuals influenced by non-Eurocentric Philosophies. However, the influences of Indigenous Philosophies present in Pragmatism and Philosophy of Process that influenced Felix Guattari and Gilles Deleuze, these influenced by Pierre Clastres who ethnographed Indigenous societies against the centralizing state so dear to Europe. Such criticisms produced Isabelle Stengers, Bruno Latour, Tim Ingold who bring new perspectives to Anthropology and Sociology, as well as Milton Santos who brought a new Geography. These movements helped us to outline the Attachinking proposal, as organizer of the multiplicity composed of beings with multiscalar and fractal diversity, common in Indigenous Philosophies, which we can use as a tool in the decolonization of Eurocentric thinking.